Faktor yang Berhubungan dengan Pemeriksaan Triple Eliminasi pada Kunjungan 1 oleh Ibu Hamil - Prita Maharani; Tuti Meihartati (Poltekkes Kemenkes Padang, 2026)
The coverage of HIV testing among pregnant women at Harapan Baru Public Health Center, Samarinda City, remains low at 57% in 2024, far below the national target of 100%. This condition increases the risk of undetected mother-to-child transmission of infection. This study aimed to identify factors associated with triple elimination screening during the first antenatal visit (K1) among pregnant women in the working area of Harapan Baru Public Health Center. This was a quantitative study using a correlational analytic method with a cross-sectional design. The population consisted of all pregnant women attending K1 in June 2025, with a total sample of 50 respondents selected using total sampling. Data were collected using questionnaires and analyzed with the chi-square test. The results showed no significant relationship between education level and triple elimination screening (p=0.595). However, there were significant associations between knowledge (p=0.023; OR=5.4) and health worker support (p=0.002; OR=10.667) with triple elimination screening. The study concludes that good knowledge and positive support from health workers increase the likelihood that pregnant women will undergo triple elimination screening from the first antenatal visit.